A TEST FOR SYSTEMATIC ERRORS IN 40AR/39AR GEOCHRONOLOGY THROUGH COMPARISON WITH U/PB ANALYSIS OF A 1.1-GA RHYOLITE - AGE, ISOTOPIC DISTURBANCES, AND THE TECTONIC EVOLUTION OF WESTERN GONDWANALAND - Min K.; Mundil R.; Renne P.R.; Ludwig K.R. (My University, 2000)
Important sources of systematic error in 40Ar/39Ar dating arise from uncertainties in the 40K decay constants and K/Ar isotopic data for neutron fluence monitors (standards). The activity data underlying the decay constants used in geochronology since 1977 are more dispersed than acknowledged by previous geochronologically oriented summaries, and compilations of essentially the same data in nuclear physics and chemistry literature since 1973 have consistently produced lower estimates (and larger assigned uncertainties) of the constants for 40K -> 40Ar and 40K -> 40Ca decay. Considering also uncertainties in 40K/K, and the questionable existence of a γ-less electron capture 40K -> 40Ar decay direct to ground state, the total 40K decay constant is known to no better than +/-2% at the 2σ level.40Ar*/40K ratios for individual standards are known to better than +/-2% in some cases, but interlaboratory discrepancies of more than 2% in the 40Ar/39Ar ages of secondary standards like the Fish Canyon sanidine (FCs) suggest larger uncertainties.The very precisely determined decay constants for 238U and 235U, and the existence of quantitative internal U/Pb reliability criteria, offer an alternative basis for evaluation of both the 40K decay constants and the ages of 40Ar/39Ar standards. High precision U/Pb (zircon) and 40Ar/39Ar (alkali feldspar) data from the 1.1-Ga Palisade Rhyolite provide a highly sensitive basis for comparison. Ten U/Pb analyses on abraded single zircons as well as one analysis of six fragmented and HF leached crystals yield a 207Pb/206Pb age of 1097.6 +5.2/-5.4 Ma (95% confidence, including decay constant errors). 40Ar/39Ar incremental CO2 laser heating of single alkali feldspar grains yields nine undisturbed age spectra with error-weighted plateau ages (based on conventional decay constants and an age of 28.02 Ma for FCs) from 1086.5 +/- 4.8 Ma (RFCsF239 = 52.7740 +/- 0.3062) to 1090.4 +/- 4.3 Ma (RFCsF239 = 53.0281 +/- 0.2746) (2σ, including analytical errors only), with MSWD = 0.95. The weighted mean RFCsF239 value of these plateau steps (52.9011 +/- 0.2324), including irradiation-related errors, is inferred to reflect the eruption-age RFCsF239 value of the Palisade Rhyolite alkali feldspar.Reconciliation of the 40Ar/39Ar and U/Pb results suggests that either the age of the 40Ar/39Ar standard is older, or the 40K total decay constant is smaller, than values in current use by geochronologists. Comparison with constraints from an historic eruption indicates a total 40K decay constant of 5.37 x 10-10/yr and an age of 28.05 Ma for FCs. Further applications of this approach will provide more robust solutions and allow estimation of uncertainties.